Market concentration of Malaysia’s Islamic banking industry - Nafisah Mohammed; Abdul Ghafar Ismail; Junaina Muhammad; Suhaila Abdul Jalil; Zaleha Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2015)
The aim of this paper is to evaluate the nature and changes of market concentration in the Malaysia’s Islamic banking due to the restructuring of Islamic banking industry within the liberalization wave in the banking market. A total of 17 Islamic banks operating over the period of 2000-2010 had been considered. The structural approach framework was used to evaluate the nature and changes of market concentration in the Islamic banking industry in Malaysia. Under this approach, various market concentration indexes has been calculated from year to year basis as proposed by the industrial organizational field. Findings herein supported the structure-conduct-performance (SCP) paradigm where different concentration ratios have decreased over the study’s period where this is reflected in the greater degree of competition in the Malaysia’s Islamic banking industry. This study found an evidence that structural changes in the Islamic banking market has changed the market structure of the respective market from moderately concentrated to low concentrated market; whereby supporting the existence of competitive environment in the Malaysian Islamic banking market. Present study contributed to new knowledge in banking market concentration particularly for Islamic banking industry in the emerging economies such as Malaysia. Many past studies studying this issue had extensively examined the conventional banking system, but only several studies were on Islamic banking market. Hence, this study may enrich the existing literature on this issue, particularly for the Islamic banking industry. Policy recommendation from the findings; first, Malaysian Islamic banking industry needs a contestable market environment as to enable them to achieve better profit and efficient operation. Second, concentration ratios from this study can be used to identify the optimal number of banking firms in the Islamic banking industry.